EVALUATING THE PSYCHOMETRIC PROPERTIES OF ALLEN AND MEYER'S ORGANIZATIONAL COMMITMENT SCALE: A CROSS CULTURAL APPLICATION AMONG MALAYSIAN ACADEMIC LIBRARIANS - Abdul Karim, Noor Harun; Mohammd Noor, Noor Hasrul Nizan (Malaysian Journal of Library and Information Science, 2017)
Meyer and Allen hold that organizational commitment is a multidimensional construct comprising three components: affective, continuance and normative. This study focuses on establishing construct validity (convergent and discriminant validity) and internal reliability by applying Allen and Meyer’s organizational commitment scale among Malaysian academic librarians. Altogether 17 items comprising the measures for both affective and continuance commitment were incorporated in the questionnaire. The survey was administered on 222 academic librarians from all the nine university libraries in West Malaysia. Findings were based on the responses from 139 usable questionnaires. The findings revealed the two measures to be distinguishable from one another i.e. the measures exhibited convergent as well as discriminant validity. The findings demonstrate that Allen and Meyer’s Organizational Commitment measures are applicable to librarians in general and to academic librarians specifically.